Determinants and prognostic significance of focal myocardial fibrosis by cardiac magnetic resonance imaging in patients with mitral valve prolapse. (25th November 2020) - Constant Dit Beaufils, A.L; Huttin, O; Piriou, N; Cueff, C; Senage, T; Marrec, M; Warin-Fresse, K; Banasiak, C; Sellal, J.M; Mandry, D; Venner, C; Filippetti, L; et al.
Abstract: Background: Mitral valve prolapse (MVP) is a frequent disease that can be complicated by mitral regurgitation (MR), heart failure, arterial embolism, rhythm disorders and death. Purpose: We sought to evaluate the correlates of late gadolinium enhancement (LGE), and the prognostic significance of ventricular size, function, and LGE by cardiac magnetic resonance (CMR) imaging on cardiovascular morbi-mortality in patients with MVP Methods: We included 426 patients (54±15 years, 57% male) with MVP (trace to severe MR) between 2010 and 2019 who underwent a comprehensive echocardiography and CMR imaging. Gadolinium was injected in 411 (96%) patients. The main outcome endpoint was a composite endpoint of cardiovascular death, heart failure, new onset atrial fibrillation or arterial embolism, censored at the time of mitral valve intervention. Results: Among the 411 patients, LGE+ was found in 118 (29%; 100 myocardial wall including 78 basal inferolateral midwall, 30 papillary muscles) and was more frequent with worse MR volume and LV remodeling. Correlates of LGE in multivariable analysis were LV mass index (OR 1.02, P=0.008), moderate-severe MR (OR 2.15, P=0.017) and coronary artery disease (OR 5.8, P=0.013). At 4 years, survival without cardiovascular events was decreased in patients with LGE+ (50.0±11.9 vs 73.5±6.3%, p<0.0001). In a stepwise multivariable analysis including classical predictors of outcome, grade of MR, LA volume index and the presence of LGE on CMR imaging (HR: 2.15 [1.15–4.02], P=0.017) were associated with impaired event-free survival. Conclusion: CMR imaging provides additional information to echocardiography in the clinical work-up of MVP. Localized LV myocardial fibrosis is a predictor of cardiovascular event in MVP patients. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): DGOS (PHRCI), Fondation Cœur et Recherche